ï¿¼IMPROVING THE GRAMMATICAL ACCURACY OF ï¿¼THE SPOKEN ENGLISH OF INDONESIAN ï¿¼INTERNATIONAL KINDERGARTEN STUDENTS - Imelda Gozali; Ignatius Harjanto (TEFLIN, 2014)
The need to improve the spoken English of kindergarten students in an international preschool in Surabaya prompted this Classroom Action Research (CAR). It involved the implementation of Form-Focused Instruction (FFI) strategy coupled with Corrective Feedback (CF) in Grammar lessons. Four grammar topics were selected, namely Regular Plural form, Subject Pronoun, Auxiliary Verbs Do/Does, and Irregular Past Tense Verbs as they were deemed to be the morpho-syntax which children acquire early in life based on the order of acquisition in Second Language Acquisition. The results showed that FFI and CF contributed to the improvement of the spoken grammar in varying degrees, depending on the academic performance, personality, and specific linguistic traits of the students. Students with high academic achievement could generally apply the grammar points taught after the FFI lessons in their daily speech. Students who were rather talkative were sensitive to the CF and could provide self-repair when prompted. Those with lower academic performance generally did not benefit much from the FFI lessons nor the CF.Â